Short sea shipping industry research - Chang Wong, Patricia Isabel; García Cantillo, Carla Patricia; Hayot Smith, Nathalie Claire; Hicks Cooper, Yeniffer Anette; Ratliff H., Donald, 1943-; Ramudhin, Amar, 1961- (Panamá : Universidad Tecnológica de Panamá, 2012)
It is important to realize that road congestion, especially in Latin American countries, limits the viability of delivering products in a timely and secure manner (1). For this reason, a Short Sea Shipping system is a very appealing alternate method of transportation for commodity trade in Central America and the Caribbean. The Short Sea Shipping system developed will be designed to serve as a trading network between the countries that make up our region of study; with Panama as the hub for the SSS System. To conclude and synthesize the findings throughout the research, a viability analysis will be done to determine the routes, the fixed and variable costs, and the distances in order to have an estimate of the costs per route. This will also help in concluding if the Short Sea Shipping System will be a viable industry for future investors whom may be interested in setting up this type of business in Panama.
Abstract. -- I. Introduction. -- II. SWOT Analysis for a Short Sea Shipping System. -- III. SWOT Analysis per country. -- IV. Comprehensive SWOT analysis. -- V. Regulations and certification/Documentation required. -- VI. Trade and trend analysis. -- VII. Port analysis. -- VIII. Characteristics of the ships: Fuel consumption per mile, size, type, technologies, types of ships available. -- IX. Cost implications for vessel selection. -- X. Viability analysis. -- XI. Conclusion. -- XII. Further work. -- Appendix A. -- Appendix B. -- Appendix C. -- Appendix D. -- Appendix E.
Tesis (
Incluye trabajos citados, páginas 141-147.
MCICS
Depósito UTP.
Keywords: Transporte acuático; Distribución física de mercancías; Embarque de mercancias; Comercio exterior; Rutas comerciales; Ingeniería industrial; Tesis y disertaciones académicas; América Central; Caribe (Región); [Maestría en Ciencias en Ingeniería de la Cadena de Suministro]